Religiosity and corporate social responsibility : A study of firm‐level adherence to Christian values in the United States - Dimic, Nebojsa; Fatmy, Veda; Vähämaa, Sami (John Wiley & Sons, 2024)
This paper examines the hypothesis that religious firms are more socially responsible. By utilizing a novel measure of religiosity that reflects firm-level adherence to Christian values, we find that religiousness is positively associated with the CSR engagement of large US firms after controlling for county-level religiosity and various firm characteristics. The results indicate that religious firms have higher social and environmental responsibility scores. The positive relationship is particularly strong with respect to product responsibility, emissions reduction, and responsible use of resources. While county-level religiosity does not have any incremental effect on CSR above the influence of firm-level religiousness, we document that the positive linkage between firm-level religiosity and CSR engagement is strengthened by local religiousness. Overall, our empirical findings suggest that faith-driven corporate values may encourage socially responsible behavior.
Keywords: corporate social responsibility; religiosity; religious values; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|